Disinformation and gendered boundarymaking: Nordic media audiences making sense of "Swedish decline". (December 2022) - Edenborg, Emil
This article examines how Russian geostrategic communication is entangled in global gender politics. The aim is to understand the resonance of disinformation in relation to culturalized, ethnicized and racialized narratives of gender, or "gendered boundarymaking." The analysis is based on focus group discussions with Swedish, Danish, and Norwegian individuals, asked to share their impressions of news articles from the Russian media agency Sputnik, which all depicted Sweden as a warning example of multiculturalism and feminism gone "too far." In the discussions, participants opposed a gender equal "self" to a patriarchal immigrant "other, " narrated Sweden as a country exceptionally concerned with gender, and tapped into competing temporalities of progress and decline. The article contributes to research on geostrategic communication by showing how disinformation efforts draw upon gendered national identities and debates about gender and immigration. More importantly, the article demonstrates that such gendered boundarymaking shapes audiences' interpretations in crucial ways. Rather than viewing disinformation only from a state-centered lens of national security, in isolation from racism, Islamophobia, anti-feminism, and queerphobia within Western societies, research should acknowledge the interconnections between geostrategic communication and everyday boundarymaking. This will be pivotal to developing counterstrategies to disinformation, whether Russian or homegrown.